Hydrogen peroxide stimulates glucose uptake in myotube cells via the insulin signaling pathway - Musalmah Mazlan,; Rehanna Mansor,; Wan Zurinah Wan Ngah, (Universiti Kebangsaan Malaysia, 2010)
Recent studies suggest that reactive oxygen species (ROS) such as hydrogen peroxide (H2O2) may exert beneficial effects on health. Therefore this study evaluated the effects of H2O2 and gamma-tocotrienol (GTT), an antioxidant, on D-[2-3H]Glucose uptake by myotubes compared to insulin. Results showed that H2O2 and insulin significantly increased D-[2-3H]Glucose uptake. This was associated with an increased in Vmax but Michaelis constant (Km) of the transport system remained unchanged indicating that an increase in amount, rather than affinity, of the glucose transporter was involved in the process. Western blot studies confirmed that H2O2 increased the expressions of insulin sensitive glucose transporter, GLUT4 and also hexokinase (an enzyme which phosphorylates glucose and indirectly stimulates glucose uptake by cells). H2O2 and insulin also stimulated increased in PPAR-γ and IRS-1, which are proteins of the insulin transduction pathway. The present data however showed that GTT did not exert any effect on glucose uptake. Thus, the study showed that H2O2 mimicked insulin action in stimulating glucose uptake in myotube cells by influencing the insulin signaling pathway.